ANALISIS UPAYA SEKOLAH DALAM MENGATASI KONFLIK ANTAR SISWA DI SMAN 1 KERITANG KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Sesri Resdiani; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in Kotabaru Village Keritang Sub-district Indragiri Hilir Regency with the aim to obtain information about school efforts in resolving conflict in SMAN 1 Keritang. Some of the problems in this research are (1) How is the effort of school to overcome conflict between student in SMAN 1 Keritang Keritang Sub-district Indragiri Hilir Regency? (2) What are the constraints faced by schools in the effort to solve conflicts between students in SMA Negeri 1 Keritang Keritang Sub-district Indragiri Hilir regency? the title of this research is